Impacto emocional por la privación de libertad en paciente masculino de 48 años - Fuentes Lopez, Estefania Alexandra (2019)
The emotional impact is the effect produced by some news or situations in our mood, the deprivation of liberty consists of the criminal ordinance assigned to the person who has executed criminal actions, recruiting them regardless of their will, this is done case study with the objective of knowing the emotional impact that a person deprived of freedom may suffer, with the purpose that the person, once obtained his freedom can be functionally reintegrated into society, obtaining a better quality of life in his mental health. The case study dealt with as a topic: emotional impact due to the deprivation of liberty in a 48-year-old male patient, in order to know the affectations in the emotional area of the person, the application of several diagnostic assessment instruments was performed, Beck Depression Inventory, Hamilton's anxiety scale whose results added to the data compiled in the observation guide and the clinical history, were very valid when it came to differentiating the symptoms